The Effectiveness Of Uploaded-Recorded Video On Instagram At Second Graders’ Smai Al-Maarif Singosari For Speaking Skill On Hortatory Exposition - Asifatul Himmah; Eko Suhartoyo; Febti Ismiatun (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: The purpose of this research is to investigate the effectiveness of uploaded-recorded video on IGTV on student speaking skill at second grade of SMAI Al-Maarif Singosar. The design of this research was experimental research with types of Pre-Experimental research. The researcher focused on one class, that were XI IBB was 23. The instruments test was six topics which were chosen by the students’ self. The researcher conducted pre-test, treatment, and post-test. The data from both pre-test and post-test was analysed using t-test analysis. The score of experimental class was significantly higher than controlled class. The result of analyzing pre-test score and post-test showed that significant level of 0.000 for first test and 0.001 for second test which less than 0.05. it means that using uploaded-recorded on Instagram was effective in improving speaking skill at second graders’ of SMAI Al-Maarif Singosari. It can be concluded that the student who was taught using uploaded-recorded video on Instagram was better than student before using uploaded-recorded video on Instagram for speaking skill as it helped the students to improve their speaking performance and speaking skill, so it could improve their speaking achievement.Keywords: Speaking Skill, Uploaded-Recorded on IGTV